Desarrollo legislativo del derecho a la vivienda digna en Colombia 1991-2011 - Frías Rubio, Carlos Mario (Temas Socio-Jurídicos, 2013)
Desarrollo legislativo del derecho a la vivienda digna en Colombia 1991-2011